Depressive Symptoms among Fourth Form Students in St. Kitts and Nevis High Schools. (2009) - Lowe, Gillian A.; Lipps, Garth; Halliday, Sharon; Morris, Amrie; Clarke, Nelson; Wilson, Rosemarie N.
Abstract : There has been limited research on depressive symptoms among high school students in St. Kitts and Nevis. This project examines levels of depressive symptoms among fourth form (grade 10) students attending all high schools in St. Kitts and Nevis. Students enrolled in the fourth form during the 2006/2007 academic year in all high schools were administered the Beck Depression Inventory II (BDI-II). A near census of the students was conducted (n = 744 students; 50.4% females, 47.6% males, and 2% no gender reported; age 13–19 years, mean = 15.5 ± 0.8 years). Six in every ten students (62.1%) reported some symptoms of depression, with 14.8% reporting moderate to severe and 9.7% reporting severe symptoms of depression. Females reported significantly higher BDI-II scores (t(727) = 7.11, p < 0.01) with 70% of females reporting some level of depressive symptoms compared with 52% of their male counterparts ( X 2 (1) = 24.6, p < 0.05). Additionally, 34% of females were in the moderate to severe or severe range of depressive symptoms, while 15% of males were in the same range. Students who were older than expected for their grade (i.e., 17 years or older) reported significantly higher BDI-II scores (F(2, 740) = 2.88, p < 0.05) than students who were younger or at the expected age (i.e., 14–16 years). Students whose mothers had a high school or postsecondary education reported significantly lower levels of depressive symptoms than students whose mothers had less than a high school education (F(3, 637), = 4.23, p < 0.05). Symptoms of depression among fourth form students in St. Kitts and Nevis are a prevalent problem that is influenced by students' age, gender, and social class as indicated by maternal education.